Relationship between perceived paternal and maternal parenting styles and student academic achievement in selected secondary schools - Elias, Habibah; Tan, Huey Yee (Eurojournals, 2009)
The purpose of this study was to examine the relationship between perceived paternal and maternal parenting styles (permissive, authoritarian, and authoritative) and students’ academic achievement (Form Three public examination results). The sample consisted of 247 Form Four students in two secondary schools. The data were collected using questionnaire. Results showed that majority of the students perceived both their father (n = 200) and mother (n = 197) as authoritative. The findings revealed that perceived paternal permissive, authoritarian, and authoritative parenting styles were not significantly correlated with students’ academic achievement. The findings also revealed that perceived maternal permissive, authoritarian, and authoritative parenting styles were not significantly correlated with students’ academic achievement. Implications of the study were discussed and recommendations for future research were suggested.